The diet of the Weddell Seal Leptonychotes weddellii at the Danco Coast, Antarctic Peninsula - Casaux, Ricardo Jorge (2006)
The diet of the Weddell Seal Leptonychotes weddellii at the Danco Coast, Antarctic Peninsula, was investigated by the analysis of 105 and 39 faeces collected at beaches surrounding Cierva Point during January–March 1998 and 2000, respectively. The diet was diverse and composed of both pelagic and benthic-demersal organisms. Fish, followed by cephalopods, constituted the bulk of the diet by number and mass. Among fish, Pleuragramma antarcticum, Chaenodraco wilsoni and Gobionotothen gibberifrons were the dominant fish by mass in 1998, whereas Chionodraco rastrospinosus, P. antarcticum and C. wilsoni predominated by mass in 2000. The contribution of channichthyid species to the diet of seals at the Danco Coast was higher than previously reported. Besides those species, the myctophid Electrona antarctica was also an important prey by number in the diet of seals in both summer seasons. The results are compared with information from other study areas and the possibility of using information on the diet of this seal as a gross indicator of fish availability/distribution is considered.